THE INFLUENCE OF SERVICE QUALITY DIMENSIONS ON PUBLIC SATISFACTION AND POLICE IMAGE SOUTH BARITO DISTRICT - Gajali, Gajali; Abdul Kadir (Sean Institute, 2020)
The image of the police is an indication of public trust in companies or institutions, and the satisfaction by the community is affected by several factors, including service quality consisting of physical evidence (tangible) response (responsiveness), reliability, empathy, and assurance. Some of these factors greatly change Community Satisfaction and Police Imagery variables. The objective of this study is to analyze and validate the influence of service quality which consists of physical evidence, responses, reliability, empathy, and guarantees to public satisfaction and the image of the police. To complete the objectives of the study, the researchers used technical path analysis and assisted using the SPSS 25 application. Including the respondents as a sample of 100 people with primary data collected through questionnaires with a measurement scale of variables the Likert scale. Furthermore, the results of this study confirm that the physical evidence variable has a clear effect on community satisfaction of 0.286% and the image of the police force of 0.129%. The responsiveness of reliable answers has a direct effect of - 0.076% and the image of the police force of 0.000%. The reliability variable directly influences the community satisfaction by 0.258% and towards police image by 0.305% empathy variable precisely influences community satisfaction by 0.115% to police image by 000%. The assurance variable has a straight effect on community satisfaction by 0.455% and the image of the police force by 0.209%. Moreover, community satisfaction affects the image of the police force 0.389%.